Consumption in Ireland: Evidence from the household budget surveys, 1994-95 to 2004-05 - Petra Gerlach-Kristen (The Economic and Social Research Institute (ESRI), 2012)
This paper analyses consumption in Ireland using household survey data. Studying surveys from 1994-95, 1999-2000 and 2004-05, we find that the median non-mortgage household tended to consume more than disposable income in the 1990s but apparently started spending in line with income by 2004-05. The initial high consumption may reflect expected income growth at the time. Mortgage households seem to have consumed in line with income in the 1990s but to have started saving by 2004-05. This may relate to the increase in the average mortgage size. A closer analysis of the 2004-05 survey shows that households receiving their income entirely from state transfer payments seemed to consume their disposable income, and sometimes more. Renters tended to consume more than they earned, while higher mortgages depressed consumption.
Keywords: 330; consumption; Ireland; Household Budget Survey; housing bubble